Development Of Student Religious Attitudes During The Covid-19 Pandemic - Ifham Choli; Ahmad Rifa’i (At-Tarbiyat, 2021)
The Covid-19 pandemic has changed the paradigm and method of learning in Indonesia, including programs for developing religious attitudes. Activities that usually take place face-to-face must change direction to be online-based. This new method is not easy to implement because it requires adaptation from all parties with this distance learning system. School innovation and development are needed so that children continue to show good religious attitudes during this pandemic. The purpose of this research is to find the right way to instil the spiritual attitude of students during the pandemic. The scope of this research is the attitude of religiosity among students during the Covid-19 outbreak. The research methodology used in this study is a qualitative research method with observation-based data collection techniques. The research results show that the development of religious attitudes among students of SMP Muhammadiyah 13 Jakarta during the Covid-19 pandemic was running quite effectively with an indication that 80% of students could pray and recite the prayer readings according to HPT Muhammadiyah well. Recommendations for further research are to focus on the use of technology in learning to help realize students' religious attitudes in schools.